Study and Analysis of Some Impact on GDP of Nepal by Increase the Exports and Decreasing Import, on Economic Growth of Nepal with the Help of Exponential Function - Sah, Aanand Kumar; Sah, Deepak Kumar; Sah, Mukesh Kumar; Sahani, Suresh Kumar; Sahani, Kameshwar; Mandal, D.N.; Karna, S.K. (FONDATIA, 2024)
In this project aims to analyze the impact of increasing exports and decreasing import on economic growth in Nepal Using an exponential function model. By examine the relationship between exports, imports and GDP, we seek to provide insights into how Nepal can enhance its export Competitiveness and reduce import dependency to stimulate economic development. By analyzing the best opportunities field which is possible in Nepal and trying to do enhance that field all over the world and as result researching on a impact of that opportunities which is possible in Nepal at export, import and GDP of Nepal. It is provider rarified by numerically with the help of exponential function.